Spot On For Liars! How Public Scrutiny Influences Ethical Behavior - Andreas Ostermaier; Matthias Uhl (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2017)
We examine in a lab experiment whether people are more honest in public than in private. We find that outcome-minded subjects lie less in public to conform with expectations about others' behavior, which are ironically false. Rule-minded subjects, in turn, do not respond to public scrutiny. These findings challenge the common faith in public scrutiny to promote ethical behavior. While public scrutiny can improve ethical behavior, this effect is contingent on people's mindsets and expectations.
Keywords: D63; 330